Defining service quality for tramp shipping - Lai, Alan Che Xiang (2011)
The purpose of this research project is to address the gap of few literature being done to define and attribute the determinants of service quality in tramp shipping sector (dry and liquid bulk). For that reason, a new conceptual model that illustrates the service quality desirable by tramp shippers from the service providers is being proposed and tested.A review is done on the literature of the three main themes, namely (1) Total Quality Management (TQM), quality awards and ISO standards; (2) Service quality in service industry and (3) Service quality in tramp shipping to allow us to formulate the new conceptual SQ model.